2018
DOI: 10.1590/s1517-707620180004.0598
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation in simulated soil of HDPE/pro-oxidant/rice husk composites: application in agricultural tubes

Abstract: The use of agricultural waste, such as rice husk (RH), for the production of cheap and eco-friendly polymer composites has emerged as a promising field of interest. The aim of this work was the preparation of highdensity polyethylene (HDPE)-based composites reinforced with rice husk and an organic pro-oxidant (EG15) for the production of seedlings tubes. Photodegradation and degradation tests in simulated soil were performed for 90 and 180 days in order to study the decomposition of these composites. The SEM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It was observed that the cross-sections of polymers and composites on the ABS and PMMA matrices had an appearance characteristic of amorphous polymers (lamella-like structure and ductility) [ 27 ]. The microstructure of the HDPE polymer cross-section was relatively flat and smooth, with visible areas of the microfibril existence [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the cross-sections of polymers and composites on the ABS and PMMA matrices had an appearance characteristic of amorphous polymers (lamella-like structure and ductility) [ 27 ]. The microstructure of the HDPE polymer cross-section was relatively flat and smooth, with visible areas of the microfibril existence [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another example of agricultural application is the use of biodegradable materials to produce tubes (containers used in the production of seedlings). There are already commercially available tubes of biodegradable seedlings, but they still do not meet the target dynamics of forest seedling production, as they have low mechanical strength, present cracks, and deformation of the tube structure, making handling difficult during application and transport to the field 70 . Several researchers have hence been trying to develop green materials based on biodegradable polymeric composites with a variety of lignocellulosic matrices, such as wood dust, 71 and rice husk, 70 among others.…”
Section: Main Applicationsmentioning
confidence: 99%